Conceptual Framework of Business Intelligence Analysis Academic Environment using BIRT - Julaily Aida, Jusoh; Raja Hasyifah, Raja Bongsu; Nazirah, Abd Hamid; Roslinda, Muda (2012)
The growth of technological development in information technology has caused challenges for many institutions. The enhancements of capabilities to gather and store data in multiple source system make it more difficult for the management in academic institutions to analyze the important data. The objective of this paper is to analyze students’ academic achievement based on accommodation factor, in other words, to analyze how accommodation can affects the students’ academic achievement. This paper discusses the conceptual framework for business intelligence analysis in academic environment using BIRT tool. BIRT tool will generate a report which illustrate and analyze the comparison of students’ academic achievement between the students that stay either in-campus and out-campus.